The thickness of posterior cortical areas is related to executive dysfunction in Alzheimer's disease (Clinics, 2014)
OBJECTIVE: To establish whether alterations of brain structures in Alzheimer's disease are associated with executive dysfunction. METHODS: Nineteen patients with Alzheimer's disease and 22 older control subjects underwent a comprehensive evaluation. The clock drawing test, digit span test, executive motor function test, Behavioral Assessment of the Dysexecutive Syndrome battery (Rule Shift Cards test), and Stroop test were used to evaluate executive dysfunction. A multiparametric approach using the FreeSurfer image analysis suite provided a description of volumetric and geometric features of the gray matter structures. RESULTS: The cortical thickness maps showed a negative correlation between the Behavioral Assessment of the Dysexecutive Syndrome battery (Rule Shift Cards test) and the right middle frontal gyrus; a positive correlation between the executive motor function test and the left superior parietal gyrus, left middle temporal gyrus, bilateral supramarginal gyri, right middle frontal gyrus, and right precuneus; a negative correlation between the Stroop test (part III) and the right superior parietal gyrus; and a negative correlation between the Stroop test (part III) and the right middle temporal gyrus. CONCLUSION: Executive dysfunction in Alzheimer's disease is correlated with alterations not only in the frontal areas but also within many temporal and parietal regions.